Synthesis of highly ordered nanorod arrays 9Mn1CeMOs and character of high sulfur capacity for hot coal gas desulfurization. Issue 4 (17th January 2014) - Liu, B.S.; Guo, Y.H.; Zhang, Q.L.; Zhang, F.M.; Zhao, X.H.
<x xml:space="preserve">Abstract</x> Highly ordered nanorod arrays 9Mn1Ce metal oxides (MOs) were prepared by negative replication of SBA‐15 hard template and were used directly for hot coal gas desulfurization at 600°C. The results indicated that 9Mn1CeMOs sorbent presented a superior desulfurization activity and small resistance of H2S diffusion compared with 9Mn1Ce mixed oxides. The breakthrough sulfur capacity (19.03 g‐S/100 sorbent) was significantly higher than that (7.94 g‐S/100 sorbent) over LaxFeyOz/MCM‐41 due to highly ordered nano‐rod array structure. The five successive sulfidation/regeneration cycles verified that 9Mn1CeMOs exhibited highly durable regeneration ability. The morphology and structure of the 9Mn1CeMOs were characterized by scanning electron microscopy, high‐resolution transmission electron microscope, X‐ray diffraction, and N2 adsorption, it revealed that parallel nanorod arrays formed with a diameter of 6–7 nm and the nanobridges between the nanorods played a crucial role for the stability of 9Mn1CeMOs. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 1266–1273, 2014